Advances in hydrogels based on dynamic covalent bonding and prospects for its biomedical application. (5th October 2020) - Ye, Jing; Fu, Shuwen; Zhou, Shiya; Li, Mohan; Li, Kaiyu; Sun, Wei; Zhai, Yinglei
Graphical abstract: Current advances of hydrogels based on dynamic covalent bonding including: developing preparing techniques; classic or unique materials applied in the hydrogels' preparation; their special properties of self-healing and responsive; and their biomedical application prospects in drug delivery, tissue engineering, wound dressing and biosensor. Abstract: In the past few decades, hydrogels based on dynamic covalent bonding (DCB) have attracted extensive attention and exploration with the rapid development of polymer science and life science disciplines. The strategies of designing DCB hydrogels are more mature, the materials for constructing DCB hydrogel skeletons come from a wider range of sources and the techniques of introducing DCB are more flexible and controllable as well. Several unique properties distinguish the DCB hydrogels from the traditional ones, for example, the autonomous healing ability and the responsiveness under some environmental stimuli. On account of these properties, DCB hydrogels are considered as one of the smart materials exhibiting great feasibility to apply in the biomedical field even though remaining some challenges to be conquered in the future. Herein, this review mainly highlights: the developing techniques of preparing DCB hydrogels, the materials of DCB hydrogels preparation, the special properties of DCB hydrogels and the biomedical application prospects for DCB hydrogels.